SHORT CONTRARIAN INVESTMENT STRATEGY : PENGUJIAN WINNER-LOSER ANOMALY PADA SAHAM-SAHAM DI BURSA EFEK INDONESIA - Widiastuti, Ekaningtyas; Jaryono, Jaryono (Faculty of Economics and Business Universitas Jenderal Soedirman, 2011)
This research is aimed to examine the winner-loser anomaly based on the overreaction hypothesis that can be decided whether the contrarian investment strategy in the short term can be applied in Indonesia Stock Exchange to obtain the return. The overreaction hypothesis is a manifestation of the inefficiency of the market (De Bondt and Thaler, 1985). Research on Short Contrarian Investment Strategy used a sample of 23 shares in the company's property and real estate sectors. The data used is stock price during the period of 2004-2008. Results obtained by using market-adjusted abnormal return indicates that the average six-month test period only loser in the stock portfolio return reversal happens. This research also examines the possibility of other factors that could explain the market overreaction return reversal, namely size and risk control. Results obtained using regression Zero Cost Investment Portfolio with the method of size and risk adjusted returns indicates that average during the six month test period showed that the loser stocks can not provide a return that is higher than the winner stocks. Thus the research indicates only loser anomaly, this is caused by an overreaction to the bad news. So it can be said that there is no potential for profit if the short-term contrarian strategy applied to the property and real estate sectors in BEI.